Molecular Characterization of Secreted Factors and Extracellular Vesicles-Embedded miRNAs from Bone Marrow-Derived Mesenchymal Stromal Cells in Presence of Synovial Fluid from Osteoarthritis Patients - Enrico Ragni; Carlotta Perucca Orfei; Federico Valli; Luigi Zagra; Laura de Girolamo (Biology, 2022)
Bone marrow-derived mesenchymal stromal cells (BMSCs)-based therapies show a great potential to manage inflammation and tissue degeneration in osteoarthritis (OA) patients. Clinical trials showed the ability to manage pain and activation of immune cells and allowed restoration of damaged cartilage. To date, a molecular fingerprint of BMSC-secreted molecules in OA joint conditions able to support clinical outcomes is missing; the lack of that molecular bridge between BMSC activity and clinical results hampers clinical awareness and translation into practice. In this study, BMSCs were cultured in synovial fluid (SF) obtained from OA patients and, for the first time, a thorough characterization of soluble factors and extracellular vesicles (EVs)-embedded miRNAs was performed in this condition. Molecular data were sifted through the sieve of molecules and pathways characterizing the OA phenotype in immune cells and joint tissues. One-hundred and twenty-five secreted factors and one-hundred and ninety-two miRNAs were identified. The combined action of both types of molecules was shown to, first, foster BMSCs interaction with the most important OA immune cells, such as macrophages and T cells, driving their switch towards an anti-inflammatory phenotype and, second, promote cartilage homeostasis assisting chondrocyte proliferation and attenuating the imbalance between destructive and protective extracellular matrix-related players. Overall, molecular data give an understanding of the clinical results observed in OA patients and can enable a faster translation of BMSC-based products into everyday clinical practice.